"Staphylococcal tricuspid valve endocarditis in a toddler with no risk factors; a rare case report". (December 2020) - Chandrasekar, S.; Satapathy, A.K.; John, J.
Abstract: Infective Endocarditis in a healthy heart is a rare occurrence, especially one involving the right side. Here we report a 3 years old girl who presented to us with continuous, high fever for 1 month with hepatosplenomegaly. Though the initial cardiovascular examination was normal, she developed a grade 2/6 pansystolic murmur heard best in the left lower parasternal area subsequently during the hospital stay. Echocardiography done showed vegetations on the tricuspid valve and the blood culture grew methicillin-sensitive Staphylococcus aureus . Thus a diagnosis of Tricuspid Valve Endocarditis (TVE) was made and antibiotics changed as per sensitivity. In view of persistent fever, a repeat echocardiography was done after 10 days, which showed no decrease in the vegetation size; hence the child was referred for definite surgical repair. Highlights: Suspect Infective Endocarditis in children with fever without focus, even in a structurally normal heart. In an infective endocarditis there is not necessarily a heart murmur that may be present during clinical examination. Echocardiography is warranted in all children with unexplained fever since the disease has a complicated and stormy course if the diagnosis and intervention are delayed. Early surgery might be required to prevent complications and ensure a quick recovery.